Effect of Rotational Speed on The Production Capacity of Bamboo Charcoal Particle Sieving Machine - Joharwan, Johanes Wawan; Palmiyanto, Martinus Heru (JMPM (Jurnal Material dan Proses Manufaktur), 2020)
Tujuan dari penelitian ini adalah untuk mempelajari pengaruh kecepatan rotasi pada mesin pengayak untuk kapasitas produksi ayakan partikel arang bambu. Mekanisme pengayakan sedang dikembangkan. Ayakan menggunakan 100 dan 200 mesh dengan kecepatan rotasi digunakan 120 rpm, 150 rpm dan 180 rpm selama 15 menit untuk mengayak 50 gr partikel arang bambu. Dalam penelitian ini, proses pengayakan dapat menghasilkan kapasitas produksi ayakan partikel arang bambu 18,78 gr pada 200 mesh dengan kecepatan rotasi 180 rpm.The aim of this research is to study the effect of rotational speed on the sieving machine for the production capacity of bamboo charcoal particle sieve. A new sieving mechanism is developed. The sieves used 100 and 200 mesh with rotational speed used 120 rpm, 150 rpm and 180 rpm for 15 minutes to sieve 50 gr of bamboo charcoal particle. In this research, the sieving process can produce production capacity sieve of bamboo charcoal particle of 18.78 gr at 200 mesh with rotational speed of 180 rpmÂ Â